A simulation study of the influence of dedicated building exits on the evacuation patterns of vulnerable populations - Yu Qiao; Qingzhao Li; Qi Liu; Jinghong Wang (Emergency Management Science and Technology)
In recent years, vulnerable populations have become the main targets of casualties in many building fire accidents. It is of great significance to study the behavioral patterns of vulnerable populations during emergency evacuation and to design specialized strategies conducive to the evacuation of vulnerable populations to improve evacuation efficiency and reduce casualties. In this paper, simulations are carried out using AnyLogic based on a social force model to explore the impact of dedicated exits in public places on the evacuation of vulnerable populations. A model of a normal room with three exits was created in which pedestrians were divided into two categories: normal and vulnerable populations with different evacuation speeds and footprint sizes. Simulation results show that dedicating middle exits reduces evacuation time in most cases while dedicating side exits significantly increases evacuation time. Middle exits as dedicated exits can balance the evacuation speed of vulnerable and normal populations, and improve the overall evacuation efficiency of vulnerable populations. Calculating the balance analysis index OPS for building evacuation, the results show that the balance of exits is the key to the evacuation time, and the closer the OPS value is to 0 the better the evacuation balance, which leads to a shorter evacuation time. This paper illustrates the impact of dedicated exits on the evacuation of vulnerable populations. Also, it provides a basis for the need for dedicated exits in different situations by calculating OPS values.